Professional practice following regulatory change: An evaluation using principles of "Better Regulation" - Lynch, Matthew; Kodate, Naonori (Research in social and administrative pharmacy, 2020)
The provisions in place internationally to regulate the practice of healthcare professionals have undergone significant change. However, this changing regulatory environment as experienced by healthcare professionals in the practice setting has not to date been widely researched. To describe the “lived experience” of pharmacists in community practice in Ireland of the model of regulation introduced by the Pharmacy Act 2007 and their perception of it as fulfilling the seven principles of “better regulation”: Necessity; Effectiveness/Targeted; Proportionality; Transparency; Accountability; Consistency and Agility. 20 community pharmacists purposively selected, shared their lived experiences of the Act, as implemented in a semi-structured interview. A qualitative content analysis incorporating a framework analysis based on the seven principles of better regulation was used to analyze the data. The Act and its implementation by the Pharmaceutical Society of Ireland (PSI) was not perceived by community pharmacists overall as fulfilling the principles of better regulation. While there was agreement that the Act was necessary, its implementation by the PSI was not viewed as being effective, targeted, proportional and consistent. The PSI was considered to act as a deterrence regulator that is not adequately transparent or accountable. The Act is not sufficiently agile to respond to changes in pharmacy practice. Community pharmacists acknowledge the need for the Pharmacy Act but perceive that the PSI needs to adopt a more responsive approach to implementation if the Act is to be considered a model of better regulation. The study findings are of interest as there is little published research on how regulation is experienced by healthcare professionals who are subject to its provisions. The principles of better regulation provide an effective qualitative methodology to examine models of professional regulation based on the “lived experience” of regulatees.